CORPORATE ACTION ON PLASTIC POLLUTION (THE BODY SHOP CASE STUDY) - Einjella Patsy; Muhammad Lukman Baihaqi Alfakihuddin; Natasha Angelica Butar Butar; Priscilla Nethania (Jurnal Ekonomi, 2023)
In recent years, plastic waste has resulted in numerous negative environmental impacts. To mitigate these effects, businesses have been adopting sustainable practices, including the production of eco-friendly products. The Body Shop, a well-known cruelty-free beauty brand, has implemented its corporate social responsibility initiative, "Bring Back Our Bottle," which aims to encourage customers and the public to recycle empty plastic packaging at their local stores. However, the success and impact of this program have yet to be fully determined. To assess its effectiveness, a qualitative research study will be conducted using a combination of online observation, data collection, and interviews with a "Sustainability Associate" and a Value Manager at The Body Shop. The findings will provide insight into the impact of the "Bring Back Our Bottle" program on plastic waste reduction. The results of this study, which indicate a significant influence on HDPE plastic waste reduction, will be useful for future marketers seeking to optimize their corporate social responsibility strategies.